Biochemical Characterization and Phylogenetic Analysis of the Virulence Factor Lysine Decarboxylase From Vibrio vulnificus - Han, Lifen; Yuan, Jinjin; Ao, Xiulan; Lin, Shujin; Han, Xiao; Ye, Hanhui (Frontiers in Microbiology, 2018)
Lysine decarboxylase (EC 4.1.1.18) catalyzes the decarboxylation of lysine to produce cadaverine. The inducible lysine decarboxylase CadA is an important enterobacterial acid stress response enzyme. Vibrio vulnificus is an extremely virulent human pathogen causing gastroenteritis, which must survive exposure to inorganic and organic acids in the stomach and small intestine. A gene encoding CadA was identified from V. vulnificus. Subsequent analyses showed that CadA from V. vulnificus (VvCadA) is a decamer with a subunit molecular mass of 82 kDa. VvCadA was purified to homogeneity after expression in Escherichia coli. VvCadA catalyzed lysine decarboxylation with an optimal pH of 6.0 and a temperature optimum of ≈37°C. The apparent Vmax and Km for lysine were 9.45±0.24 U/μg and 0.45±0.05 mM. The mutation analysis suggests that the amino acid binding pyridoxal phosphate, the cofactor of the enzyme, plays a key role in the reaction. Mutation of the negatively charged residues interacting lysine also affects the activity of the enzyme to some extent. Quantitative reverse transcription-PCR revealed that expression of VvcadA was up-regulated under low pH, low salinity, and oxidative stresses. Furthermore, concentrations of cadaverine released to the cell exteriors were also increased under the stresses. The protein sequence similarity analysis indicated that lysine decarboxylases with ornithine decarboxylases and arginine decarboxylases are highly conserved and that horizontal gene transfer plays a role in the evolution. Hence, our data provide evidence for the biochemical characteristics and important roles of VvCadA under stress conditions.